Android-Based Studio Fitness Application Design on Lifespa Fitness - Wahyu Joko Saputro; Supriadi Panggabean; Ahmad Rifqi (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2024)
The rapid advancement of smartphone technology, particularly with operating systems like Android, has facilitated the development of diverse mobile applications that deliver accessible and functional information. As a widely used platform, Android supports innovative solutions to address user needs in various domains. Fitness, as a structured form of exercise utilizing specialized equipment and techniques, aims to help individuals achieve a proportional and healthy body. Despite its popularity, many people lack knowledge about proper training methods and remain unaware of fitness centers in their vicinity. This challenge is particularly pronounced among beginners, who may feel hesitant to exercise alone. Furthermore, fitness enthusiasts often seek opportunities to exercise with friends or partners to enhance their experience. This study employs a combination of observation, interviews with relevant stakeholders, and literature reviews to gather data and insights for developing the Lifespa Fitness Android-based application. The application serves as a comprehensive fitness information hub, providing users with essential details such as membership procedures, pricing, class schedules, and the location of Lifespa Fitness. Designed with efficiency and user accessibility in mind, the application enables users to access fitness-related information conveniently anytime and anywhere via their smartphones. The development of this application not only addresses the knowledge gap in proper training methods but also fosters greater engagement in fitness activities by making information readily available and promoting social interaction among fitness enthusiasts. This research contributes to the digital transformation of the fitness industry, offering a scalable and user-friendly solution that enhances public health awareness and encourages a more active lifestyle.